Toksisitas Ekstrak n-heksana Serbuk Gergaji Kayu Sengon (Albizia falcataria l. Forberg) terhadap Mortalitas Serangga Penggerek Buah Kopi (Hypothenemus hampei ferr.) (Scolytidae: Coleoptera) - Purwatiningsih Purwatiningsih; Firna Putri Mandasari; Susantin Fajariyah (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
Research on the toxicity of n-hexane extract of Albizia falcataria sawdust against Hypothenemus hampei has been conducted. The method of research was contact method. The concentrations used in the experiment were control (aquadest); 0.25%; 0.5%; 1%; 2%; and 4%. Every concentration was sprayed on the female imago. Observations were performed 120 hours after treatment. The results showed that there was an effect of the length of observation time and concentration on the mortality of H. hampei (GLM Test α= 5%). The time of observation and concentration of A. falcataria sawdust n-hexane extract has positive correlation on H. hampei mortality. Therefore, the longer the treatment time, the more H. hampei mortality is increased. The mortality of H. hampei also increased with increasing concentration given. At a concentration of 4%, extract of A. falcataria sawdust has high toxicity which causes the highest mortality (> 92%).